Organizational Behavior Factors On The Usefulness Of The Regional Financial Accounting System With Cognitive Conflict As An Intervening Variable - Yuliarti, Annisa Gayuh; Widyarti, Maria Theresia Heni; Ciptaningtias, Arum Febriyanti (Jurnal Akuntansi dan Pajak, 2025)
Abstract This research aims to analyze and determine the effect of organizational behavioral factors, namely training and clarity of purpose on the usefulness of the regional financial accounting system with cognitive conflict as an intervening variable at Dinas Kesehatan Kota Semarang. This research uses interviews and questionnaires as data collection methods. The questionnaire employs a Likert scale, and the sample for this research consists of 30 respondents, with the sample criteria being employees of government agencies who perform accounting and administrative functions. The analysis tools used include validity test, reliability test, descriptive statistical analysis, classic assumption test, hypothesis test, and the sobel test. The research findings indicate that training has no effect on the usefulness of the regional financial accounting system. Similarly, cognitive conflict does not affect the usefulness of the regional financial accounting system. Clarity of purpose has an effect on the usefulness of the regional financial accounting systems. Training does not affect the usefulness of the regional financial accounting system with cognitive conflict as an intervening variable. Clarity of purpose does not affect the usefulness of the regional financial accounting system, with cognitive conflict as an intervening variable Keywords : Training, Clarity of Purpose, Cognitive Conflict, Usefulness of the Regional Financial Accounting Systems